Forms of intertextuality in a postmodern play (a case study of “Old Money” by Wendy Wasserstein) - Ostropalchenko, Yulia (Studia Philologica, 2024)
The study is devoted to the analysis of forms of intertextuality in postmodern drama on the example of Wendy Wasserstein's play “Old Money”. Postmodernism, as a cultural paradigm, is characterized by complex relations with its own history and traditions. The article explores how the use of various texts, allusions, and cultural references in “Old Money” contributes to the creation of a multilayered and complex text characteristic of postmodern drama. By analyzing the intertextual relations in this play, the purpose of the article is to reveal the peculiarities of Wasserstein's postmodern creative approach and their influence on the perception and interpretation of the playwright's text. The results of the study may be useful for further understanding of intertextual strategies in postmodern literature and studying postmodern aspects in the work of Wendy Wasserstein. The study of intertextuality in “Old Money” allowed us to better understand and evaluate the artistic world of the play, to reveal the relationship between texts and contexts that interact in creating meaning. We have identified the features and significance of each of the intertextual allusions, as well as their impact on the perception and interpretation of the play. In addition, the analysis of intertextual connections shed light on the specificity and value of the author's own creative method, revealing his cultural and intellectual preferences. Key words: intertextuality, postmodernism, allusion, drama.